2003
DOI: 10.1021/jf0341619
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Extraction of Essential Oils from Perovskia atriplicifolia Benth.

Abstract: The supercritical fluid extraction (SFE) of the aerial parts of Perovskia atriplicifolia Benth. was studied. The effect of different parameters such as pressure, temperature, modifier identity, and modifier volume on the SFE of the plant was investigated. The extracts were analyzed by GC and GC-MS and compared with the essential oil obtained from P. atriplicifolia Benth by steam distillation. The supercritical extracts and the steam-distilled products had very different compositions. The main constituents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…For volatile oil extraction through SC CO 2 , small changes in temperature can cause significant changes in solubility with a non-linear relationship [156]. Whereas the operative pressure is the main parameter that influences the fluid density and therefore the solvent power of supercritical fluid, the effect of temperature depends on the nature of plant material and has to be determined case by case [157].…”
Section: Process Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For volatile oil extraction through SC CO 2 , small changes in temperature can cause significant changes in solubility with a non-linear relationship [156]. Whereas the operative pressure is the main parameter that influences the fluid density and therefore the solvent power of supercritical fluid, the effect of temperature depends on the nature of plant material and has to be determined case by case [157].…”
Section: Process Considerationsmentioning
confidence: 99%
“…Studies about the effects of co-solvents at constant pressure and temperature evaluated the extraction efficiency of different modifiers at increasing percentages for volatile oil extractions. The addition of methanol, ethanol or halogenated co-solvents reduces the number of extracted terpenes with respect to pure SC CO 2 for Perovskia atriplicifolia but increases the extraction selectivity [157]. However, the use of co-solvents, especially at high percentages, leads to a biphasic system that will change the critical parameters of the mixture.…”
Section: Process Considerationsmentioning
confidence: 99%
“…The small lavender flowers have a sweet flavor and may be eaten in salads or used as a garnish. This species is also suitable for use in forming a decorative hedge of moderate height (Pourmortazavi, 2003). It is a favorite aromatic shrub for honey bees, with the honey made by bees fed on this shrub being colorless and having a typical flavor and aroma.…”
Section: Introductionmentioning
confidence: 99%
“…The supercritical fluid extraction (SFE) of the aerial parts of P. atriplicifolia has also been studied with the major components of SFE extracts being 1,8-cineol limonene, camphor, b-caryophyllene, d-cadinene, a-pinene, and a-terpinyl acetate (Pourmortazavi, 2003). Furthermore, in their studies, the main constituents of the same oil obtained by steam distillation were found to be 1,8-cineol camphene, and a-humulene (Pourmortazavi, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of different compositions can be obtained by different extraction methods applied to natural products (20)(21)(22)(23)(24). The GC-MS profile of the ethyl acetate extract is shown in Figure 2.…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%